Plasmodium falciparum coinfection is associated with improved IgE and IgG3 response against hookworm antigens. Issue 4 (14th June 2022) - Sakyi, Samuel A.; Wilson, Michael D.; Adu, Bright; Opoku, Stephen; Brewoo, Antwi; Larbi, Amma; Baafour, Emmanuel K.; Tchum, Samuel K.; Saahene, Roland O.; Aniagyei, Wilfred; Sewor, Christian; Courtin, David; et al.
Abstract: Background: Plasmodium falciparum and Hookworm infections are prevalent in West Africa and they cause iron deficiency anemia and protein malnutrition in Children. Immune response of these parasites interact and their interactions could have repercussions on vaccine development and efficacy. The current goal of hookworm eradication lies on vaccination. We evaluated the effect of P. falciparum coinfection and albendazole treatment on naturally acquired antibody profile against hookworm L3 stage larvae antigen. Methods: In a longitudinal study, 40 individuals infected with Necator americanus  only, 63 participants infected with N. americanus and P. falciparum,  and 36 nonendemic controls (NECs) were recruited. The study was done in the Kintampo North Metropolis of Ghana. Stool and blood samples were taken for laboratory analyses. Serum samples were obtained before hookworm treatment and 3 weeks after treatment. Results: The malaria‐hookworm ( N. americanus and P. falciparum ) coinfected subjects had significantly higher levels of IgE ( β  = 0.30, 95% CI = [0.12, 0.48], p  = 0.023) and IgG3 ( β  = 0.15, 95% CI = [0.02, 0.52], p  = 0.004) compared to those infected with hookworm only ( N. americanus ). The N. americanus groups had significantly higher levels of IgG3 ( β  = 0.39, 95% CI = [0.14–0.62], p  = 0.002) compared to the control group. Similarly, N. americanus and P. falciparum coinfected participants had significantly higher levels of IgE ( β  = 0.35, 95% CI = [0.70–0.39], p  = 0.002) and IgG3 ( β  = 0.54, 95% CI = [0.22–0.76], p  = 0.002). Moreover, albendazole treatment led to a significant reduction in IgE, IgA, IgM, and IgG3 antibodies against hookworm L3 stage larvae ( p  < 0.05) Conclusion: P. falciparum is associated with improved IgE and IgG response against hookworm L3 stage larvae. Treatment with single dose of albendazole led to reduction in naturally acquired immune response against hookworm infection. Thus, P. falciparum infection may have a boosting effect on hookworm vaccine effectiveness.